- UPAYA DEBITUR UNTUK MEMPEROLEH RISALAH LELANG EKSEKUSI HAK TANGGUNGAN: - - Wieke Septiani Putri; Sri Untari indah Artati (Faculty of Law, Universitas Trisakti, 2023)
Agraria, in the narrow sense, pertains to land as the subject of mortgage rights. When a debtor defaults, the land is executed. However, the auction process conducted by PT BANK BNI without providing a notice of auction to the debtor who granted the mortgage rights, as regulated in PERMENKEU Number 213/PMK.06/2020, has become a subject of debate. This research is a normative legal study, employing descriptive analysis and utilizing secondary data. The data is qualitatively analyzed with deductive conclusions. The research findings indicate that the auction process that does not provide a notice of auction to the debtor is in accordance with the provisions of PERMENKEU Number 213/PMK.06/2020. However, the judge relies on a legal basis that is not appropriate, namely UUPK and POJK Number 1/POJK.07/2013, whereas it should be based on UUHT and PERMENKEU Number 213/PMK.06/2020. Debtors are no longer considered consumers of BANK BNI if the auction notice is issued by KPKNL. The efforts of the debtor regarding the auction of land rights are not in line with PERMENKEU Number 213/PMK.06/2020, as there is no provision stating that the owner of the property has the right to obtain a copy of the auction notice